2012
DOI: 10.1094/mpmi-06-12-0148-ta
|View full text |Cite
|
Sign up to set email alerts
|

A Draft Genome Sequence ofNicotiana benthamianato Enhance Molecular Plant-Microbe Biology Research

Abstract: Nicotiana benthamiana is a widely used model plant species for the study of fundamental questions in molecular plant-microbe interactions and other areas of plant biology. This popularity derives from its well-characterized susceptibility to diverse pathogens and, especially, its amenability to virus-induced gene silencing and transient protein expression methods. Here, we report the generation of a 63-fold coverage draft genome sequence of N. benthamiana and its availability on the Sol Genomics Network for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
395
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 437 publications
(413 citation statements)
references
References 69 publications
2
395
0
1
Order By: Relevance
“…Because clathrin has been shown to function in BRI1 endocytosis (9), we addressed genetically whether clathrin is required for the internalization of PRRs. To overcome potential genetic redundancy, we knocked down the six CLATHRIN HEAVY CHAIN (NbCHC) constructs found in the N. benthamiana genome (25) by transient expression of a single hairpin construct (Fig. S7A).…”
Section: Resultsmentioning
confidence: 99%
“…Because clathrin has been shown to function in BRI1 endocytosis (9), we addressed genetically whether clathrin is required for the internalization of PRRs. To overcome potential genetic redundancy, we knocked down the six CLATHRIN HEAVY CHAIN (NbCHC) constructs found in the N. benthamiana genome (25) by transient expression of a single hairpin construct (Fig. S7A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, members of the Solanaceae serve as model systems for investigating fundamental processes involved in plant growth and development, including the ripening of fleshy fruit (tomato), tuber formation (potato), pollination and petal senescence (petunia), plant pathogen and pest interactions (tomato, potato, and Nicotiana spp), and the biosynthesis of specialized metabolites (tomato, pepper, Nicotiana, Hyocyamus, Datura, and Atropa spp). The development of genomics tools, including genome sequences and transcriptome data sets for several of these model species, is facilitating characterization of these biological processes (Xu et al, 2011;Ashrafi et al, 2012;Bombarely et al, 2012;Tomato Genome Consortium, 2012;Kim et al, 2014;Qin et al, 2014). In this study, a deep transcriptome of A. belladonna, a member of the Solanaceae family often used for investigating tropane alkaloid biosynthesis (Suzuki et al, 1999a(Suzuki et al, , 1999bRothe et al, 2003;Richter et al, 2005), was generated from diverse tissues, facilitating in silico quantitative analyses of gene expression (Tables 1 to 3).…”
Section: Discussionmentioning
confidence: 99%
“…Resequencing confirmed that the S. lycopersicum M82 SlIPMS3 also contains this truncation, indicating that this is a bona fide change rather than a sequence assembly error. Because introgression of the S. pennellii LA0716 region containing this gene has a major impact on acyl chain composition, we attempted to identify the orthologous gene from this accession using available sequence data (Bombarely et al, 2012;Tomato Genome Consortium, 2012;Bolger et al, 2014a). The SlIPMS3 (Solyc08g014230) and S. pennellii (Sopen08g005140) genes are reciprocal best hits, with 97% identity within a large syntenic region comprising 361 collinear genes (see "Materials and Methods").…”
Section: Identification Of a Novel Trichome-expressed Ipms Genementioning
confidence: 99%